Model Antecedents, Behaviour and Consequences (ABC) of Social Media Information and Compulsive Panic Buying Relationship to Buying Decisions : A Conceptual Framework - Eman Sulaiman; Erwan Iskandar; Vina Andita Pratiwi (International Journal of Ecma Science, 2021)
Nowadays, it's all about social media. Antecedents - Based on the results of the analysis of previous studies, researchers categorized antecedents for marketers by using social media as a marketing communication tool. Viral marketing is one of the advantages of social media over traditional media. Second: Buzz Marketing uses WOM to share consumer experiences, opinions, or information about a brand or company with fellow social media users. In social media users whose recommendations are often or trusted by other social media, users are called influencers or opinion leaders. There are several consequences or results that can be generated through social media marketing, including increased brand awareness, increased reputation, increased relationships, brand development, and increased purchase intention